Improving Land Sector Governance in The Gambia - Bensouda, Amie (World Bank, Washington, DC, 2017)
The Land Governance Assessment Framework (LGAF) is a diagnostic tool to assess the status of land governance at country level using a participatory process that draws systematically on existing evidence and local expertise rather than on outsiders. The analysis covers nine themes: land tenure recognition; rights to forest and common lands and rural land use regulations; urban land use, planning, and development; public land management; process for transfer of public land to private use; public provision of land information (land administration and information systems); land valuation and taxation; dispute resolution and review of institutional arrangements and policies. The assessment follows a scorecard approach and produces a matrix of policy priorities matrix. The LGAF process helps to establish a consensus on (i) gaps in existing evidence; (ii) areas for regulatory or institutional change, piloting of new approaches, and interventions to improve land governance on a broader scale (e.g. by strengthening land rights and improving their enforcement); and (iii) criteria to assess the effectiveness of these measures. This report presents the result for The Gambia.